Foliar application of phytohormones enhances growth of maize and soybean seedlings - Llanes, Analía; Iparraguirre, Julia; Masciarelli, Oscar; María, N.; Luna, Maria Virginia (Ediciones INTA, 2019)
Phytohormones such as gibberellins, auxins and cytokinins are plant growth promoting factors which added to foliar fertilizers can modulate plant growth and development of agricultural species. This work was performed to study the effects of exogenously applied phytohormones both alone and in mixtures, on a legume and a cereal growing in chambers with controlled conditions of humidity, temperature and light/dark cycle. It was found that application of phytohormones resulted in a considerable increase in growth of soybean and maize plants. The mixture of phytohormones formulated with the lowest concentration of each required to enhance plant growth, allowed a significant improvement on several growth parameters involved in productivity. Thus, the addition of this mixture to commercial products as foliar fertilizers may render potential improvement of legume and cereal yields.